Psychological capital and work engagement among strawberry generation employees - Khoiriah, Farihatul; Viranda, Chintia (Universitas Ahmad Dahlan, 2024)
Organizations require energetic and dedicated employees to achieve their goals through work engagement. Work engagement can be influenced by the unique characteristics of the strawberry generation, especially when combined with psychological capital. This study aims to determine the impact of psychological capital (self-efficacy, optimism, hope, and resiliency) on work engagement among strawberry generation employees. The research employs a quantitative method, measured using the Psychological Capital Questionnaire 24 (PCQ-24) and the Utrecht Work Engagement Scale 17 (UWES-17). The population used in this study consists of employees in Indonesia, from which 227 samples were selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression analysis. The results of this study are: (1) there is no effect of self-efficacy on work engagement among strawberry generation employees, (2) there is a positive effect of optimism on work engagement among strawberry generation employees, (3) there is a negative effect of hope and resiliency on work engagement among strawberry generation employees, and (4) there is a positive effect of psychological capital on work engagement among strawberry generation employees.